Trask's historical linguistics - Millar, Robert McColl (Hodder Arnold, 2007)
Written in an engaging style and illustrated with examples from a wide range of languages, this book is an introduction to historical linguistics - the study of language change over time
Rev. ed. of: Historical linguistics / R.L. Trask. London : Arnold, 1996
Keywords: Comparative linguistics; Historical linguistics